Membrane Bound CRT Fragment Accelerates Tumor Growth of Melanoma B16 Cell In Vivo through Promoting M2 Polarization via TLR4 - Hong-Min Wang; Zhe Zhou; Jie Miao; Bo Zhu; Xiao-Qiu Dai; Qiao Zhong; Fang-Yuan Gong; Xiao-Ming Gao (Journal of Immunology Research)
Calreticulin (CRT) is a major calcium-binding luminal resident protein on the endoplasmic reticulum that can also be released extracellular as well as anchored on surface of cells. Previously, we demonstrated that soluble recombinant CRT fragment 39-272 (CRT/39-272) exhibited potent immunostimulatory effects as well as immunoregulation effects on immune cells. Here, we constructed stable B16 melanoma cell lines expressing recombinant CRT/39-272 on the membrane (B16-tmCRT/39-272) to investigate the roles of cell surface CRT on tumor progression. We found that B16-tmCRT/39-272 cells subcutaneously inoculated into C57BL/6 mice exhibited stronger tumorigenicity than the B16-EGFP control cells. The tumor associated macrophages infiltrated in tumors were mainly M2 phenotype. Regulatory T cells (Tregs) were also expanded more in bearing mice. Consistent with the in vivo results, B16-tmCRT/39-272 promoted macrophage polarization toward F4/80+CD206+ M2 macrophages and promoted transforming growth factor beta (TGF-β) secretion in vitro, which could promote naïve CD4+T cell differentiation into Tregs. These results imply that the tmCRT/39-272 could accelerate tumor development by enhancing M2 macrophage polarization to induce TGF-β secretion, and then promoted Treg differentiation in the tumor microenvironment. Our data may provide useful clues for better understanding of the potentiating roles of CRT in tumorigenesis.